MyPlate Foods to Increase: Fruits and Vegetables - Jonathan Holzinger; Karla Shelnutt; Gail Kauwell (EDIS)
Fruits and vegetables should be a main component of every meal. They are low in calories and provide a number of vitamins that you need in your diet. By making half of your plate fruits and vegetables at every meal, you will reduce your risk for chronic diseases and may even protect yourself against certain types of cancer. This 4-page fact sheet provides information on fruits and vegetables and includes tips on how to add more of them to your diet. Written by Jonathan Holzinger, Karla Shelnutt, and Gail Kauwell, and published by the UF Department of Family Youth and Community Sciences, February 2013.